2011
DOI: 10.1002/bmc.1721
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of stressed degradation products of metoprolol using LC/Q‐TOF‐ESI‐MS/MS and MSn experiments

Abstract: A rapid, specific and reliable isocratic high-performance liquid chromatography combined with quadrupole time-of-flight electrospray ionization tandem mass spectrometry (LC/Q-TOF-ESI-MS/MS) method has been developed and validated for the identification and characterization of stressed degradation products of metoprolol. Metoprolol, an anti-hypertensive drug, was subjected to hydrolysis (acidic, alkaline and neutral), oxidation, photolysis and thermal stress, as per ICH-specified conditions. The drug showed ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 6 publications
4
22
0
Order By: Relevance
“…Over the years hyphenated techniques have been increasingly used for structural characterization of degradation products of drugs and impurities against the time consuming process involved in preparative isolation of degradation products followed by spectral characterization …”
Section: Introductionmentioning
confidence: 99%
“…Over the years hyphenated techniques have been increasingly used for structural characterization of degradation products of drugs and impurities against the time consuming process involved in preparative isolation of degradation products followed by spectral characterization …”
Section: Introductionmentioning
confidence: 99%
“…Characterization of DPs and understanding of the degradation pathways are very crucial for safety and potency assessment of the drugs in clinical trials. Over the last decade, liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI‐MS/MS) in combination with accurate mass measurement has been increasingly used for the structural characterization of DPs of drugs formed under various stress conditions . For example, Shah et al have reported a study on complete degradation behavior and the identification of stressed DPs of atorvastatin using LC/MS/MS and MS n experiments .…”
Section: Introductionmentioning
confidence: 99%
“…Jain and Basniwal have reviewed the analytical techniques that are used for characterization and quantification of thresholds of impurities and DPs in various matrices . Recently, we have demonstrated the applications of LC/MS/MS, MS n experiments and accurate mass measurements for the identification and structural characterization of stressed DPs of various active pharmaceutical drugs like prulifloxacin, metoprolol, milnacipran and carvedilol . The information from the structural characterization of DPs is expected to be useful to develop new drugs with improved stability.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, hyphenated techniques such as GC‐MS and liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) have been increasingly used for structural characterization of transformation products of drugs and impurities against the time consuming process involving preparative isolation of transformation products followed by spectral characterization . The analysis involves high performance liquid chromatography/ultra high performance liquid chromatography (HPLC/UHPLC) method development for the separation of TPs from the drug followed by structural characterization of the TPs using LC‐MS/MS in combination with elemental compositions of ions derived from their accurate masses.…”
Section: Introductionmentioning
confidence: 99%